Analysis of mortality by cardiovascular disease subgroups in Brazil before and during the COVID-19 pandemic (2000–2022) by sex and age group - Cicero Emanoel Alves Leite; Raphael Mendonça Guimarães; Andréa Sobral (Revista Brasileira de Epidemiologia, 2025)
ABSTRACT Objective: To analyze the effect of the COVID-19 pandemic on mortality by cardiovascular disease (CVD) subgroups in Brazil, considering sex and age group. Methods: Ecological time-series study with secondary data from the Mortality Information System for the period 2000-2022. Age-adjusted mortality rates per 100,000 inhabitants were calculated and joinpoint regression models were used to estimate rate trends. Results: Mortality from CVD in Brazil between 2000 and 2022 showed a decrease in ischemic heart disease (IHD) and cerebrovascular disease (CBVD), while other CVD showed an unstable behavior, increasing after 2020. The reduction in IHD was more pronounced until 2020, decelerating thereafter. CBVD continued to decline but at a slower pace. Other CVD, after a downward trend, showed a significant increase (+3.8% per year), possibly because of the pandemic. Women had a greater reduction in mortality, especially due to IHD. Intermediate age groups (40-59 years) showed a decrease until 2020 but recorded increases after this period, reinforcing the impact of the pandemic. In 2021, all subgroups showed excess mortality: 8% for CBVD and IHD, and 15% for other CVD. In 2022, this pattern intensified, with values of 16% (CBVD), 18% (IHD) and 23% (other CVD). Conclusion: The COVID-19 pandemic significantly impacted CVD mortality in Brazil, changing trends according to age group, sex and disease subgroup. The study points to an inflection in mortality rates during the pandemic, highlighting the need for further investigations to understand the mechanisms involved.